The real equiangular tight frames obtained from rank 3 graphs - Bannai, Eiichi; Bannai, Etsuko; Lee, Chin-Yen; Tanaka, Hajime; Yu, Wei-Hsuan (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
We present all nontrivial real equiangular tight frames φmm=1M in RN obtained as spherical embeddings of primitive rank 3 graphs on M vertices, and those such that one of their associated M strongly regular graphs on M - 1 vertices is a primitive rank 3 graph.